External activity demands differ between referees and players during a sub-elite, men's basketball match - Leicht, A.; Fox, J.; Connor, J.; Sargent, C.; Sinclair, W.; Stanton, R.; Scanlan, A. (Research Quarterly for Exercise and Sport, 2019)
Match activity demands of basketball players have been well reported but little exists in terms of quantifying the demands encountered by referees during match-play. Potential differences between referees and players may identify different fitness capacities and subsequent need for different training regimes. Purpose: The aims of this brief report were to: 1) document the activity demands of sub-elite basketball referees during a match; and 2) compare referee and player match activity demands. Method: Three referees and six players participating in the same sub-elite, basketball match were monitored for external activity (PlayerLoad™, PL) via microsensor technology. The proportion of each quarter and entire match time spent in pre-set PL bands was also examined to develop PL profiles. Differences in activity demands between referees and players were calculated using effect size (ES) analyses (± 95% confidence intervals). Results: Referees experienced an absolute PL of 310 ± 28 arbitrary units (4.2 ± 0.4 AU.min-1) during the match which was ~40% lower than that of the players (ES = 1.14; -0.45, 2.48). Referees exhibited a match PL profile dominated by the lowest PL band (~91%) with the players' PL profile shifted slightly towards higher bands. Conclusion: Sub-elite basketball referees experienced activity demands substantially lower than that of players during the same match. Limited movement patterns due to recommended court positioning may have contributed to the lower PL of referees. Differences in PL between referees and players highlight a need to develop specific training regimes to focus on key fitness capacities for each match role.